1984
DOI: 10.1007/bf00500903
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol induces an increase of harman in the brain and urine of rats

Abstract: Harman occurs in rat brain, with the highest concentration in the cerebellum and the lowest in the striatum. 2 g/kg ethanol were ineffective with respect to the concentration of harman in the brain whereas 5 g/kg ethanol caused a time-dependent increase in the cerebral cortex as well as the cerebellum. A toxic dose (8 g/kg) of ethanol elicited no change of harman in the brain 3 h following the application. The rise in the harman concentration in the brain did not correlate with the increase of acetaldehyde in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…It is somewhat surprising that the fully aromatic compounds are probably more important than the tetrahydro compounds (25, 32,64). It remains to be elucidated whether the biosynthesis and/or the degradation of $C's are disturbed in alcoholics.…”
Section: Biologicalfunctionsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is somewhat surprising that the fully aromatic compounds are probably more important than the tetrahydro compounds (25, 32,64). It remains to be elucidated whether the biosynthesis and/or the degradation of $C's are disturbed in alcoholics.…”
Section: Biologicalfunctionsmentioning
confidence: 97%
“…The fully aromatic fiG's have been assayed by HPLC with fluorometric detection (8). Harman was found in blood plasma and erythrocytes from non-alcoholic subjects (8), in human platelets (29a, 30), in rat lung (31), brain (31,32), rat and human urine (32, 33) as well as in 1 sample out of 24 of human cerebrospinal fluid (31).…”
mentioning
confidence: 99%
“…Alcohol metabolism may lead to the formation of a beta-carboline compound called harman (33,34), and alcoholic beverages frequently contain harman (35), which has moderate affinity for MAO-A. To avoid temporary occupancy effects of harman (10), [ 11 C]-harmine PET scanning was timed at a point when harman levels were negligible (36), which was verified by plasma sampling.…”
Section: Protocol On Day Of Pet Imagingmentioning
confidence: 99%
“…Harmane alkaloids have been detected in food plants [2] such as soy, rye, wheat, rice, barley, mushrooms, grape juice, wine [6], charred insects, and cigarette smoke. It has been reported that alcohol increases the harmane content in the brain and urine [7].Cytotoxic effects of harmane alkaloids have also been found [8]. These alkaloids are reported to affect the cardiovascular system [9, 10] and to have a hypotensive effect [10].…”
mentioning
confidence: 98%
“…Harmane alkaloids have been detected in food plants [2] such as soy, rye, wheat, rice, barley, mushrooms, grape juice, wine [6], charred insects, and cigarette smoke. It has been reported that alcohol increases the harmane content in the brain and urine [7].…”
mentioning
confidence: 99%